Humanized Mice for the Evaluation of Novel HIV-1 Therapies - Abeynaike, Shawn; Paust, Silke (Frontiers in Immunology, 2021)
With the discovery of antiretroviral therapy, HIV-1 infection has transitioned into a manageable but chronic illness, which requires lifelong treatment. Nevertheless, complete eradication of the virus has still eluded us. This is partly due to the virus's ability to remain in a dormant state in tissue reservoirs, ‘hidden’ from the host’s immune system. Also, the high mutation rate of HIV-1 results in escape mutations in response to many therapeutics. Regardless, the development of novel cures for HIV-1 continues to move forward with a range of immunotherapy approaches to gene editing. However, to evaluate in vivo pathogenesis and the efficacy and safety of therapeutic approaches, a suitable animal model is necessary. To this end, the humanized mouse was developed by McCune in 1988 and has continued to be improved on over the past 30 years. Here, we review the variety of humanized mouse models that have been utilized through the years and describe their specific contribution in translating HIV-1 cure strategies to the clinic.